Sulfasalazine efficacy and tolerability in rheumatic diseases - V. V. Badokin (Научно-практическая ревматология)
Sulfasalazine is one of the main disease modifying drugs for the treatment of chronic inflammatory joint and spine diseases. The article describes mechanism of action of sulfasalazine and its main metabolites. Detailed information about anti-inflammatory and immunosuppressive action of the drug is presented. Results of many studies of sulfasalazine efficacy in rheumatoid arthritis, ankylosing spondylitis, psoriatic arthritis and reactive arthritis are discussed from the evidence based medicine point of view. Data on sulfasalazine tolerability and safety are presented with separate discussion of hypersensitivity and dose-dependent adverse reactions so as their treatment and prophylaxis.